O professor articulador e o atendimento dos alunos em situação de dificuldade de aprendizagem matemática em escolas estaduais de Cuiabá-MT - Couto, Brígida (2016)
This research was conducted at the Graduate Program in Education, in line Education in Science and Mathematics Education at the Federal University of Mato Grosso-UFMT, by the Group of Studies and Research in Mathematics Education (GRUEPEM) and its main objective: Investigate the conceptions of articulators teachers on teaching and learning mathematics and learning difficulties in mathematics students in the early years of primary education in state schools in Mato Grosso. First performed a literature study to indicate theoretical aspects related to the difficulties of learning mathematics, understand the conceptions regarding mathematics teaching-learning process in the school context and the organization of state schools of the State of Mato Grosso. For the theoretical composition and better interpretation of the data we have based Chabanne (2006), Darsie (1999), ARROYO (1999), Castro (2009), among others. We used as a qualitative methodology approach of interpretative supported mainly Bogdan and Biklen (1994). The research was conducted in three state schools in the city of Cuiabá MT. The study subjects were three articulators teachers and three coordinators. As research analysis tools include: documents provided by schools, questionnaires and interviews to articulators teachers and coordinators. As categories for data analysis considered the traditional approach and the constructivist and a category that emerged from the course of our research, and the quality of teaching and learning mathematics process. Initial searches for contact with the research subjects showed a lack of articulators teachers in schools and the difficulty for the implementation of the joint room in this context. The analysis of P. P. P. and Articulation room to project documents reveal. that none of the schools included work with the difficulties of learning mathematics in conjunction room, on the grounds that there is a greater need for students to overcome the difficulties in reading and writing. After the contraction of the articulators, already in May, we had the opportunity to produce data on their conceptions and after examination it was revealed that the conceptions both for teaching and learning, and for learning disability in mathematics tend to move between the two approaches, traditional and constructivist, explored in this research. The coordinators show, in an interview, the fact that there are weaknesses in mathematics teaching-learning process and the need to improve the quality of education, not even contemplating mathematics for care. These data demonstrate the fragility of the schools, and reinforce the need to work in conjunction room covering all the difficulties. Show although the quality in the teaching-learning process is compromised, since the work with mathematics has been neglected. They also reveal that the teacher articulator is important in this context and should be a greater mobilization by the school and SEDUC to the immediate presence of this professional at the beginning of the school year.